Proceeding of 1st Libyan conference on Medical and Pharmaceutical Sciences 2017 - Atia, Ahmed (AlQalam Journal of Medical and Applied Sciences, 2017)
Welcoming speech of 1st LMsC 2017 By Dr. Ahmed Atia Conference president We are delighted to have you here to participate and share in the 1st Libyan Medical Sciences conference 2017 hosted by University of Tripoli Alahlia [UTA]. Thank you for coming. I first wish to extend to you the greetings of the conference committee. It was this body, being responsible for establishing and organizing this work and allowed us to solve the all-important pharmaceutical and health problems. The 1st LMsC aimed to widen the students beyond their field of study while creating and expanding various network of cooperations in the field of research between our institution and other leading organizations. LMsC will highlight many interdisciplinary sciences related to Medical and Pharmaceutical sciences, the situations in which integration from all these elements will create a holistic approach to word the betterment of Medical and Pharmaceutical sciences in the future. I wish also to thank the dean of UTA, Dr. Sherren Njeam, for her support. And before I give the speech to our coordinator for of this conference, I want to say once more on behalf of the committee, welcome. It’s a pleasure to see so many of you here.